2015
DOI: 10.4103/0975-7406.163537
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of curcumin as an adjunct to scaling and root planning in chronic periodontitis patients: A clinical and microbiological study

Abstract: Background and Objectives:Curcumin is a naturally occurring anti-inflammatory agent with various biologic and medicinal properties. Its therapeutic applications have been studied in a variety of conditions, but only few studies have evaluated the efficacy of curcumin as local drug delivery agent and in the treatment of periodontitis. The present study was to evaluate the efficacy of the adjunctive use of curcumin with scaling/root planing as compared with scaling/root planing alone in the treatment of the chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 16 publications
2
31
0
10
Order By: Relevance
“…[5][6][7] CURC is a natural compound with promising effects in modulating the osteo-immuneinflammatory and antioxidant host response both in periodontally diseased sites [14][15][16][17]21,22 and in diabetes and related complications. 19,20 For the first time, this investigation assessed the natural curcumin's Although promising effects of natural CURC on periodontal tissues have already been revealed in earlier experimental 14,16,17,27 and also clinical studies, 28,29 only few information is available concerning the influence of a chemically modified CURC on periodontitis in the presence of a recognized at-risk condition as diabetes mellitus 21,22 as employed in the current study) has already proved to be promising as a host modulatory agent in periodontal disease pathogenesis and to reduce the alveolar bone loss related to periodontitis. 16,17 In fact, evidence from previous studies supports that the dysregulation of osteo-immune-inflammatory biomarkers, a known effect of diabetes, may be a contributing factor in the development of periodontal bone loss.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[5][6][7] CURC is a natural compound with promising effects in modulating the osteo-immuneinflammatory and antioxidant host response both in periodontally diseased sites [14][15][16][17]21,22 and in diabetes and related complications. 19,20 For the first time, this investigation assessed the natural curcumin's Although promising effects of natural CURC on periodontal tissues have already been revealed in earlier experimental 14,16,17,27 and also clinical studies, 28,29 only few information is available concerning the influence of a chemically modified CURC on periodontitis in the presence of a recognized at-risk condition as diabetes mellitus 21,22 as employed in the current study) has already proved to be promising as a host modulatory agent in periodontal disease pathogenesis and to reduce the alveolar bone loss related to periodontitis. 16,17 In fact, evidence from previous studies supports that the dysregulation of osteo-immune-inflammatory biomarkers, a known effect of diabetes, may be a contributing factor in the development of periodontal bone loss.…”
Section: Discussionmentioning
confidence: 96%
“…The outcomes of the morphometric evaluations of the current study revealed that DM induction promoted higher periodontal disease progression and that diabetic rats treated with daily CURC + INS, as well as those Non‐DM, presented lower linear bone loss values in periodontitis sites, suggesting that the combined use of CURC and INS, and not the substances used alone, may positively influence periodontal breakdown, even in the presence of DM. Although promising effects of natural CURC on periodontal tissues have already been revealed in earlier experimental and also clinical studies, only few information is available concerning the influence of a chemically modified CURC on periodontitis in the presence of a recognized at‐risk condition as diabetes mellitus and there are no data revealing the impact of a natural CURC in the progression of EP associated with DM. Of importance, although some evidence has suggested that certain chemically modified CURC shows improved solubility and bioavailability in comparison with natural CURC, advantages related to the natural form of CURC include the facility to obtain the substance and greater possibility of using this therapeutic agent for clinical application in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of curcumin in decreasing MMP-2 and MMP-9 expression levels was reported in cancer cells, such as squamous cell carcinoma and osteoclastoma (Cao et al , 2015, Lee et al , 2015). Additionally, in vivo studies in humans and animals demonstrated curcumin’s effectiveness in decreasing the severity of periodontal diseases (Elburki et al , 2014, Nagasri et al , 2015, Bakir et al , 2016, Elburki et al , 2016). Curcumin has been investigated in many clinical trials for treatment of several disorders, such as ulcerative colitis (Baliga et al , 2012), breast cancer (Nagaraju et al , 2012), pancreatic cancer (Veeraraghavan et al , 2011), and diabetes (Abdel Aziz et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therapy for periodontitis aims to reduce the pathogenic bacteria found in dental plaque to slow or arrest periodontal disease progression [6]. Conventional treatment methods are mechanical eradication of bacterial plaque included scaling and root planning (SPR), but the effectiveness of SPR is limited in inaccessible areas to periodontal instruments [7]. Local antimicrobial agents are used as an adjuvant factor in the clinical therapy [8].…”
Section: Introductionmentioning
confidence: 99%